Interfaith Marriage and the Submission of One Spouse: Should District Courts Legalize It? - Maharani Christy Anggraeni; Nugraheni, Destri Budi; Dzahaby, Ja’far Al (Pandecta Research Law Journal, 2024)
This research investigates the legal complexities surrounding interfaith marriages in Indonesia, particularly focusing on the concept of self-submission as outlined in the Supreme Court's fatwa Number 231/PAN/HK.05/1/2019. The study explores the validity of interfaith marriages from the perspective of Islamic, Christian, Catholic, Buddhist, Hindu, and Confucian religious laws. It also examines the role of district court judges in determining the validity of such marriages based on self-submission. The findings reveal significant disparities in legal interpretations, with judges who support the legalization of interfaith marriages considering them valid when conducted according to religious procedures that permit interfaith unions. However, judges opposing such marriages reference the prohibitions inherent in the religious laws of one of the spouses. The novelty of this research lies in its analysis of the intersections between religious law and civil law in determining the validity of interfaith marriages in Indonesia, especially the concept of self-submission. The study underscores the urgency of creating a clear, unified legal framework that addresses interfaith marriages, balancing respect for religious beliefs with the need for legal certainty. Nationally, this research contributes to ongoing debates about religious freedoms, marriage equality, and the role of the judiciary in interpreting religious norms within the broader legal system. Globally, it adds to the discourse on how countries with diverse religious populations navigate the intersection of tradition, modernity, and legal recognition of interfaith unions, offering comparative insights into the challenges faced by similar jurisdictions.